212k views
4 votes
Solve for n

–6(n – 8) = 4(12 – 5n) + 14n

show work please!

User Kristiyan
by
4.8k points

2 Answers

6 votes

Explanation:

-6(n-8)=4(12-5n)+14n

-6n+48=48-20n+14n

20n-6n-14n=48-48

-6n+6n=0

-6n=-6n

The statement is true for any value of n, because both sides are identical.

n€ R.

...

wait ... is this a graphical question ?!?!?!

User Kurt Friars
by
5.0k points
5 votes

Hello!

The answer is:

The solution is all the values that belong to the real numbers, and any value of "n" that we can substitute, will lead us to a satisfied equation.

Why?

We are given the following expression:


-6(n-8)=4(12-5n)+14n

So, we need to perform the expressed operations using the distributive property, and then, add/subtract the like terms.

Now, solving we have:


-6(n-8)=4(12-5n)+14n


-6*n+(-6*-8)=4*12+(4*-5n)+14n


-6n+48=48-20n+14n


-6n+48=48-6n


0=0

Hence, we can se that 0 is equal to 0, it means that the solution is all the values that belong to the real numbers, and any value of "n" that we can substitute, will lead us to a satisfied equation.

Have a nice day!

User MikeNereson
by
5.0k points